Multi-Actors' Co-Implementation of Climate-Smart Village Approach in West Africa: Achievements and Lessons Learnt - Bayala, Jules; Ky-Dembélé, Catherine; Dayamba, Djibril S; Somda, Jacques; Ouédraogo, Mathieu; Diakité, Adama; Chabi, Adéyèmi; Alhassane, Agali; Bationo, B. André; Buah, Saaka S.J.; Sanogo, Diaminatou; Tougiani, Abasse; et al. (Frontiers Media, 2021)
Climate change and variability are significant challenges for the environment and food security worldwide. Development strategies focusing simultaneously on adaptive farming, productivity, and reducing greenhouse gas (GHG) emissions-known as climate-smart agriculture (CSA) strategies-are key to responding to these challenges. For almost a decade, within the framework of Climate Change, Agriculture and Food Security (CCAFS), World Agroforestry (ICRAF), and its partners have been using Participatory Action Research (PAR) to fully engage key stakeholders in co-creating such CSA development strategies. This includes the testing of Agricultural Research for Development (AR4D) CSA scalability options. The multidisciplinary teams include the National Research and Extension Systems (NARES), national meteorological services (NMS), non-profit organizations (NGOs), and local radio programs, among others. The CCAFS-West Africa Program, World Agroforestry-West and Central Africa (ICRAF-WCA), International Union for Conservation of Nature (IUCN), University of Reading, and Centre Régional de Formation et d'Application en Agro-météorologie et Hydrologie Opérationnelle (AGRHYMET) provide technical backstopping to the national teams. Climate information (CI) was used as an entry point to inform the development of CSA technologies and practices within Climate-Smart Villages (CSV). This groundwork has led to a greater understanding of three critical factors for successful CSV implementation: (1) Building strong partnerships to co-design and develop agricultural systems that improve ecosystem and population resilience, (2) Key stakeholders (researchers, farmers, development agents, and students) capacity strengthening through vocational and academic training, and (3) Using CI for livelihood planning at all scales. These three factors support more effective identification and testing of agricultural technologies and practices addressing climate variability and change at plot, community, and landscape levels. This paper discusses the PAR-CSA methodology and parameters for evaluation, including biophysical and social change. Keys to success, including communication, knowledge sharing tools, and scalability are also discussed. Finally, future opportunities for improvement are presented, including knowledge product development, CSA policy and investment planning, capacity building, further engagement of the private sector, and additional research on existing practices and tools.